Diramus, a new genus of the leafhopper subfamily Evacanthinae (Hemiptera: Cicadellidae), with description of three new species from Thailand - Wang, Yang; Wei, Cong; Zhang, Yalin (Zootaxa, 2013)
Diramus, gen. nov. (Hemiptera: Cicadellidae: Evacanthinae), and three new species, Diramus khaokus sp. nov., Diramus nigromaculatus sp. nov. and Diramus uncatus sp. nov., are described from Thailand. The differences between the new genus and the closely related genus Bundera Distant is discussed.